ANALISIS KELAYAKAN INVESTASI PADA PENINGKATAN STATUS KLINIK UTAMA CAHAYA IMANI MENJADI RUMAH SAKIT TIPE D DI KABUPATEN HULU SUNGAI SELATAN PROVINSI KALIMANTAN SELATAN - Fifi Noviana,; Wahyuddin Bagenda,; Mira Veranita, (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the investment feasibility of upgrading Klinik Utama Cahaya Imani to a Type D Hospital in Hulu Sungai Selatan Regency, South Kalimantan Province. The analysis was conducted using methods such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Profitability Index (PI), and Average Rate of Return (ARR). The research method applied was a qualitative descriptive method with a case study approach, through the collection of primary and secondary data from Klinik Cahaya Imani and related agencies. The analysis showed that the investment requirement amounts to Rp 110,060,402,638 with an estimated hospital revenue of Rp 32,339,793,340 per year. The financial analysis results indicated a positive NPV, IRR higher than the discount rate, PP faster than the economic life, PI greater than one, and ARR meeting the investment feasibility criteria. Thus, upgrading Klinik Utama Cahaya Imani to a Type D Hospital is financially feasible. The results of this study are expected to serve as a basis for managerial decision- making in developing health services in Hulu Sungai Selatan Regency